An Up-to-date Review on the Classification, Pharmacology, and Production of Terpenes and Terpenoids - Shataer, Dilireba; Chang, Yuhang; Obul, Mamateli; Aierken, Kailibinuer; Liu, Haipeng (Current Organic Chemistry, 2025)
Terpenes and terpenoids, which are a large and diverse class of organic compounds, are widely distributed in many plants. In recent years, there has been a growing interest in the biosynthesis and biological activity of terpenes and terpenoids in order to fully exploit their efficacy in a wider range of applications, such as medicine, biology, flavors and fragrances, food, and cosmetics. This review aims to update and elucidate the classification, pharmacology, and production of terpenes and terpenoids, focusing on the bioactivities and biosynthetic mechanisms. Their classification methods, production routes, and potential application ranges are discussed in detail. Moreover, the research on terpenes and terpenoids since 2014 is also reviewed by identifying the trends and keywords through bibliometric analysis, classifying terpenes and terpenoids in recent studies according to their chemical structure, and summarizing their production methods and pharmacological properties. Generally, terpenes and terpenoids can be divided into five categories based on the number of isoprene units, but are highly diverse in structure. Terpenes and terpenoids exhibit various bioactivities, including anti-inflammatory, antibacterial, anticancer, and antioxidant effects, due to their structural diversity. The common production methods mainly include extraction and separation, chemical synthesis, and biosynthesis. Different approaches to biosynthesis have been proposed but have not been applied in large-scale production. With increasing medicinal potentials, the demand for terpenes and terpenoids will continue to increase, where biosynthesis will play a key role in improving their production.
Keywords: isoprene units